A numerical study on applying slot-grooved displacer cylinder to a γ-type medium-temperature-differential stirling engine. (1st February 2018) - Chen, Wen-Lih; Chen, Chao-Kuang; Fang, Mao-Ju; Yang, Yu-Ching
Abstract: In this study, the effects of heat transfer enhancement on engine performance by introducing slot grooves on walls of the displacer cylinder of a γ -type medium-temperature-differential Stirling engine have been investigated using computational fluid dynamics. Cases include smooth displacer-cylinder wall with heat source and heat sink extension on displacer cylinder circumferential wall and slot-grooved displacer-cylinder walls with grooves at different locations and numbers. The grooves are at displacer cylinder circumferential wall or at top and bottom walls. The slot grooves are classified into three types according to their locations. It is found that the circumferential wall is very important on engine's heat transfer behavior. Extending heat source and heat sink on this wall can improve indicated power but losing efficiency. Type-1 grooves enhance both positive and inadequate heat transfer, hence its effects on enhancing engine performance is mixed. In contrast, Type-3 grooves mainly enhance positive heat transfer thus yield improvement on indicated power and efficiency as the number of grooves increases. However, Type-2 grooves, which enhance heat transfer on regenerative wall, have been shown to yield the best performance. Compared with the engine without any heat-transfer-enhancement measure, a case with 96 Type-2 grooves improves indicated power up to 49%. Highlights: Study on Stirling engine heat transfer enhancement with 3 types of grooves. Type 1 grooves performance is mixed because of inadequate heat transfer. Contrary, type 3 grooves can largely reduce inadequate heat transfer. Type 2 grooves are in the regenerative channel and yield the best performance. Type 2 grooves produce about 50% increase in indicated power.